PEMEROLEHAN BAHASA ANAK USIA DINI (AHMAD JAMALUDDIN MUTHOHAR) DI KABUBATEN BANYUWANGI - Maisaroh, Siti; Hasbullah Ridwan, Muhammad (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe Ahmad Jamaluddin Muthohar's language acquisition in the fields of phonology and syntax. This research is based on the speech of two year old children who are almost perfect in using word order and language. The method used is qualitative with a descriptive type, because this research contains language acquisition in early childhood which describes its acquisition in the areas of phonology and syntax. The results of research into the acquisition of phonology on consonants and vowels can be seen in the field of phonology which shows that Ahmad Jamaluddin Muthohar has mastered consonant letters and is able to pronounce them at the beginning, middle and end of words, but he has not mastered several consonants such as [r] and [ l] which he usually replaces with the consonant [n], and the consonant [v] is replaced with [p]. The consonants [w], [f], [y] have never been heard at the end of the word, the consonant [z] has only been heard at the beginning, while [x] has not been heard at all. The conclusion of this research is that Ahmad Jamaluddin Muthohar has obtained vowels that look perfect in their pronunciation and use at the beginning, middle and end of his words. Ahmad Jamaluddin Muthohar's acquisitions in the field of syntax can be seen in the use of declarative, interrogative and imperative sentences that he has mastered